Morfologi Dan Morfometrik Spermatozoa Ayam Nunukan - Ardhani, Fikri (BIOPROSPEK: Jurnal Ilmiah Biologi, 2015)
[Artikel telah ditarik] The fertility of a rooster is not only influenced by motility,viability and DNA integrity of the spermatozoa but it isdetermined by the morphological integrity of the spermatozoa.This study objectives to determine the morphological andmorphometric spermatozoa of nunukan rooster, one ofIndonesian germplasm. Rooster’s cement was collected usingdorso-abdominal massage method. The cement was stainedwith a combination of eosin Nigrosin. The stained cement wasused to observe the morphology and measurement of the mainparameters. The morphological was evaluated using amicroscope with a magnification of 100x as many as 100spermatozoa. The spermatozoa morphometric were analyzedusing the Raster Image program and its were identified the headdimension, the head length and width, the mid-piece length, thetail length, and the ratio of the head and tail. A nunukan roosterspermatozoon in average has total length of 86.724 ± 12.496μm with a head length, the mid-piece length, the tail length is12.766±2.307 μm, 4.220±1.127 μm, and 75.738 ± 9.061 μm,respectively, while the head width is 1.391±0.244 μm, and thethe head: the tail ratio is 1: 5.9. The morphologically normalpercentage is 80.50 ± 9.40 %. In conclusion, the characteristicsspermatozoa of nunukan rooster due to morphology,morphometric, and morphologically normal percentage aspectsare within the range of other types of rooster in many previousstudies.